Henk Vinken, Yuko Nishimura, Bruce L.J. White y Masayuki Deguchi (comps.), Civic engagement in contemporary Japan. Established and emerging repertoires, Nueva York, Springer, 2010, xiv, 261 pp. - Mandujano Salazar, Yunuen Ysela (El Colegio de México, 2013)
Henk Vinken, Yuko Nishimura, Bruce L.J. White y Masayuki Deguchi (comps.), Civic engagement in contemporary Japan. Established and emerging repertoires, New York, Springer, 2010, xiv, 261 pp.